Evaluation of Antiretroviral and Tuberculosis Therapy Based on Clinical Outcomes in Patients With HIV/AIDS and Tuberculosis Co-Infection at Regional General Hospital in Denpasar - Kurnianta, Putu Dian Marani; Suwirtawati, Ni Putu Dewanty; Dhrik, Mahadri (Pharmacon: Jurnal Farmasi Indonesia, 2025)
Human immunodeficiency virus and tuberculosis (HIV-TB) co-infection presents a significant challenge in Denpasar due to high incidence and complex treatment. This retrospective single-cohort study aimed to analyze the relationship between the results of therapy evaluation and the clinical outcomes in patients with HIV-TB. Secondary data from 20 HIV-TB treatment at a Regional General Hospital in Denpasar during 2022-2024 were evaluated. Fisher’s Exact test was performed to analyze the association between adherence to antiretroviral therapy (ART) and antituberculosis therapy (ATT), as per the guidelines, and their treatment success. Results showed predominance in males of productive age (60%), with cough as the most common symptom (75%), and 80% patients at HIV stage 4. All patients (N=20) received first-line ART and ATT. However, only 20% completed the treatment algorithm and 40% achieved treatment success. Although no significant association was found between treatment evaluation and success (p = 0.101), the relevant findings in this study emphasized the important role of rational drug use based on guidelines.  Further studies with larger samples and a prospective approach are needed to explore additional factors affecting clinical outcomes of patients with HIV-TB undergoing therapy according to the established guidelines.